Peacekeeping in Sierra Leone The Story of UNAMSIL - Olonisakin, Funmi (Lynne Rienner Publishers, 2022)
The inside story of how the UN mission in Sierra Leone was transformed from an embarrassing failure into what is now widely considered one of the most successful peacekeeping missions in UN history
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Jun 2022)
Keywords: POLITICAL SCIENCE / World / African